1985
DOI: 10.1128/aem.49.1.37-41.1985
|View full text |Cite
|
Sign up to set email alerts
|

Change in Microbial Numbers during Thermophilic Composting of Sewage Sludge with Reference to CO 2 Evolution Rate

Abstract: Dewatered sewage sludge was composted in a laboratory-scale autothermal reactor in which a constant temperature of 60°C was kept as long as possible by regulating the air feed rate. The change in CO2 evolution rate was measured continuously from the start up through the cessation of composting. The succession of mesophilic bacteria, thermophilic bacteria, and thermophilic actinomycetes was also observed during the composting. Specific CO2 evolution rates of thermophilic bacteria and actinomycetes in the consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
2
4

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(36 citation statements)
references
References 14 publications
2
28
2
4
Order By: Relevance
“…While prior work has demonstrated that inoculation of organic matter with targeted degradative microbial communities can alter microbial activity and accelerate decomposition (Nakasaki et al 1985;Ichida et al 2001), little is known regarding the ecological differences that arise from differing compost inocula on a given biomass during enrichment culture. Here, two feedstocks relevant to biofuel production and two compost inocula were used for enrichment culture to gauge their effects on enriched community structure.…”
Section: Discussionmentioning
confidence: 99%
“…While prior work has demonstrated that inoculation of organic matter with targeted degradative microbial communities can alter microbial activity and accelerate decomposition (Nakasaki et al 1985;Ichida et al 2001), little is known regarding the ecological differences that arise from differing compost inocula on a given biomass during enrichment culture. Here, two feedstocks relevant to biofuel production and two compost inocula were used for enrichment culture to gauge their effects on enriched community structure.…”
Section: Discussionmentioning
confidence: 99%
“…Ashbolt and Line (1982) classified laboratory scale vessels into rotating drums and stationary cylinders. Several studies have addressed the performance of each type of vessels (Schulze, 1962;Jeris and Regan, 1973;Suler and Finstein, 1977;Ashbolt and Line, 1982;Sikora et al, 1983;Nakasaki et al, 1985;Hogan et al, 1989;Palmisano et al, 1993). Bach et al (1984) combined the advantages of these two types of vessels and used a mixed isothermal reactor.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous papers (7,9), we showed that the reaction rate of composting as measured by the CO2 evolution rate is related to microbial succession, and we estimated the specific activity for thermophilic bacteria and actinomycetes. In this paper, the effect of temperature was investigated by the same procedure as in our previous papers, under controlled environmental conditions.…”
mentioning
confidence: 99%
“…The composting temperatures were kept at 50, 60, and 70°C as long as possible by controlling the rate of airflow. The operation of the reactor and the composting procedure were the same as those described in our previous paper (7). Two experimental series of runs were performed.…”
mentioning
confidence: 99%
See 1 more Smart Citation